PENGEMBANGAN MEDIA BUKU POP-UP UNTUK KETERAMPILAN MEMBACA PEMAHAMAN BAHASA JERMAN SISWA KELAS X SMAN 2 SIDOARJO - MUSTIKARINI, SARI (LATERNE, 2016)
Based on the results of questionnaires that have been distributed in the tenth grade IIS 1 (Social Sciences) at SMAN 2 Sidoarjo and interviews with German language teacher SMAN 2 Sidoarjo, found a hard time understanding a reading. And needed media support for the German language reading skills. Therefore, it encourages researchers to develop media Pop-Up books to read German language skills. Given these media be more interesting learning so that students become more interested in understanding the content of the German-language literature. This study describes the development process Media Pop Up Books for learning the German language skills of reading comprehension class X SMAN 2 Sidoarjo The method used is the development of Research and Development (R & D) Borg and Gall in Sugiyono research steps in the approach to R & D there are ten steps of research, including: 1) the potential and problems, 2) collection of data, 3) product design, 4 ) design validation, 5) revision of the design, 6) product trials, 7) the revised product, 8) utility testing, 9) product revision, 10) mass production. The results of the analysis concluded that the development of media Pop Up Books feasible and effective use in learning the German language reading skills Understanding of class X SMAN 2 Sidoarjo .Media Pop Up Books This is feasible because it has been validated by three experts, namely one media expert and two expert material. Validation matter experts and media experts obtained a value of 82.5%, and the value of 95%, so it is generally considered very strong. And said to be effective because it is already in the test phase of product usage. Results of activity observation of teachers and students using the media Pop Up book values ??obtained 93.75% and 95%, so it is generally considered very strong. Results of activity observation of teachers and students using the media Pop Up book values ??obtained 93.75% and 95%, so it is generally considered very strong. According to Ridwan media can be said to be feasible if the results of the feasibility analysis of the media got value> 61% or categorized with the criteria of strong and very strong. Keywords: Research and Development, books Pop Up, reading comprehension.